1996
DOI: 10.1097/00042560-199607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Type Hypersensitivity Testing in Tanzanian Adults with HIV Infection

Abstract: Delayed-type hypersensitivity (DTH) testing and total lymphocyte counts as measures of cell-mediated immune function were assessed for medical patients in Dar es Salaam, Tanzania. DTH testing was performed with the Multitest CMI device which simultaneously administers seven antigens. Of 201 patients completing DTH testing, 90 were HIV seropositive. Anergy occurred more frequently among HIV-seropositive patients (39 of 90) as compared with HIV-seronegative patients (17 of 111). DTH skin test reactivity, measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The stem bark of Rhus verniciflua contains a high level of urushiols, which are polymerized formation of a lacquer film by the radical-chain reaction (Hirota et al, 1998). The exudate was previously found to have anti-AIDS, a strong antioxidant and immune-enhancing activities (Miller et al, 1996). However, its therapeutic use is undermined by the strong shown by some of the population in East Asia, especially to western.…”
Section: Introductionmentioning
confidence: 99%
“…The stem bark of Rhus verniciflua contains a high level of urushiols, which are polymerized formation of a lacquer film by the radical-chain reaction (Hirota et al, 1998). The exudate was previously found to have anti-AIDS, a strong antioxidant and immune-enhancing activities (Miller et al, 1996). However, its therapeutic use is undermined by the strong shown by some of the population in East Asia, especially to western.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of response to one or more control antigens, however, does not always mean inability to respond to PPD. In populations in which the prevalence of tuberculin reactivity is high, the percentage of persons who react to PPD may be higher than the percentage reacting to several other antigens (28,29 ). Even in populations in which the prevalence of PPD positivity is low, some persons respond to PPD testing despite lack of response to a companion antigen (19 ).…”
Section: Anergy and Interpretation Of Ppd-tuberculin Skin Testsmentioning
confidence: 99%
“…The following CDC staff members prepared this report: [27][28][29][30][31][32][33] for the use of anergy skin testing in conjunction with purified protein derivative (PPD)-tuberculin skin testing of persons infected with human immunodeficiency virus (HIV). In February 1997, CDC convened a meeting of consultants to discuss current information regarding anergy skin testing, PPD skin testing, and tuberculosis (TB) preventive therapy for HIV-infected persons.…”
mentioning
confidence: 99%
“…In the past, anergy testing was used in screening for tuberculosis. Although anergy testing is no longer recommended in routine clinical use, largely because of its limited reproducibility and other factors [12], it does provide information about the capacity of HIV-infected patients to mount an effective local immune response [13][14][15][16][17][18][19][20][21][22][23][24][25]. We have previously found that anergy status before the initiation of HAART independently predicts post-HAART morbidity and death [26,27], even after controlling for CD4 T-cell count, HIV-RNA level, and other factors.…”
Section: Introductionmentioning
confidence: 99%